2002
DOI: 10.1074/jbc.m205877200
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing and Interaction with Di- and Polyvalent Cations Control the Dynamic Range of Acid-sensing Ion Channel 1 (ASIC1)

Abstract: belong to the Deg/ENaC super family of ion channels (1). Members of this super gene family form Na ϩ -selective ion channels (P Na /P K , 8 -100) that can be blocked by amiloride (IC 50 , 0.2-20 M). All family members show some common hallmarks including two hydrophobic domains, short intracellular N and C termini, and a large extracellular loop containing conserved cysteines. Channels of this gene family probably form tetramers (2, 3).To date, six different members of the ASIC subfamily have been cloned (ASIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
265
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(284 citation statements)
references
References 32 publications
17
265
0
2
Order By: Relevance
“…Increased interstitial pH after neurostimulation has also been reported in other preparations (11,42,47). Previous studies showed that raising extracellular pH before an acid stimulus reduced steady-state inactivation and increased the amplitude of ASIC currents (43,44,48). Thus, alkalinization might prepare postsynaptic ASICs for subsequent stimuli, and thereby maximize their current.…”
Section: Epsp (% Of Baseline)mentioning
confidence: 90%
See 1 more Smart Citation
“…Increased interstitial pH after neurostimulation has also been reported in other preparations (11,42,47). Previous studies showed that raising extracellular pH before an acid stimulus reduced steady-state inactivation and increased the amplitude of ASIC currents (43,44,48). Thus, alkalinization might prepare postsynaptic ASICs for subsequent stimuli, and thereby maximize their current.…”
Section: Epsp (% Of Baseline)mentioning
confidence: 90%
“…The alkalinization that followed the transient acidification has been reported in other preparations (11). Because ASICs inactivate in the continued presence of protons (39,(42)(43)(44), alkalinization between synaptic release stimulations might function to resensitize the receptor.…”
Section: Presynaptic Stimulation Increases Extracellular Protons and mentioning
confidence: 99%
“…However, probing deactivation kinetics at more acidic pHs is hampered by steady-state inactivation (20,38). For example, in a standard theta-tube application experiment, a resting pH of 7.2 produces extensive steady-state inactivation, making responses in outside-out patches small and difficult to evaluate.…”
Section: Resultsmentioning
confidence: 99%
“…The deactivation kinetics of ASIC1a to brief applications of acidic solution were recently examined by jumping ASIC1a-containing outside-out patches from a baseline pH of 8.0, followed by a jump to pH 5.0 for 1 ms and then a return to pH 8.0 (20). Under such conditions, ASIC1a deactivation kinetics were surprisingly brief, given their reported single-channel open times (37) and high apparent affinity for protons [pH evoking half the maximal response (pH 50 ) of 6.4-6.6, EC 50 of 400-250 nM (38)(39)(40)]. However, as mentioned above, during intense neuronal activity or stimulation, the interevent synaptic cleft pH does not toggle between neutral and acidic pH in a binary fashion.…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, the molecular identity of the channels was uncertain. Moreover, in some cases, permeability was measured by varying Ca 2ϩ and Na ϩ concentrations in the presence of other monovalent and divalent cations; this result could limit the accuracy of the determinations, especially for a channel that may not only conduct Ca 2ϩ but also be regulated by it (38,39). Our studies of recombinant channels indicate that ASIC1a can carry Ca 2ϩ current; an advantage of these studies is that Ca 2ϩ was the only abundant extracellular cation.…”
Section: Discussionmentioning
confidence: 99%